Peluang Penerapan Produksi Bersih pada Industri Tepung Sagu - Maulidia, Vera; Jati, Dian Rahayu; Apriani, Isna; Bhaskara, Renaldi Surya; Firmansyah, Muhammad (Universitas Diponegoro, 2020)
Increased demand for processed sago has an impact on increasing sago starch production. The opportunity to produce sago flour is then used by some entrepreneurs to produce on a factory scale. Increasing competitiveness among entrepreneurs causes many aspects to be needed to improve marketing quality, including efforts to reduce waste generated from each production process. This study aims to identify the production process of sago starch and provide recommendations for waste minimization and clean technology in the sago flour industry. Interview methods and field observations were carried out in this study. The volume of waste generated in the production process of sago flour includes 10 kg of used sacks, 10 kg of spilled lamantak, 100 kg of sago dregs, 60 kg of spilled sago flour, 20 kg of burning ash and 50 kg of coarse sago flour. Liquid waste in the form of used water is 36,042 liters. Clean production methods that can be done are reducing the use of washing water, reselling used sacks into handicrafts, returning spilled flour and coarse sago flour to the demolition and dispensing basins, selling burning ashes, selling sago dregs for duck livestock feed and processing production liquid waste. using IPAL with a minimum capacity of 5,000 liters. The method offered can reduce the use of clean water by 2,358 liters of the total water requirement of 38,400 liters once produced